1993
DOI: 10.1159/000129279
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in Renal Function during Laparoscopic Cholecystectomy

Abstract: Intraoperative serial changes in systemic hemodynamic parameters and in the results of renal function tests were studied in 7 patients who underwent laparoscopic cholecystectomy (LAP) in which intra-abdominal pressure was maintained at 12 mm Hg, and in 7 patients who underwent minilaparotomy cholecystectomy (MINI). No significant changes were observed in the parameters in the MINI group during the operation. However, urine output, effective renal plasma flow and glomerular filtration rate in the LAP group were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 9 publications
1
32
0
2
Order By: Relevance
“…The absence of an increase in vasopressin levels during PP is an interesting finding since vasopressin has previously been shown to increase considerably, in some studies to more than 70 times its initial levels, during CO 2 PP [2,7,19]. One possible explanation is that the blood samples were not taken in chilled tubes.…”
Section: Discussionmentioning
confidence: 95%
“…The absence of an increase in vasopressin levels during PP is an interesting finding since vasopressin has previously been shown to increase considerably, in some studies to more than 70 times its initial levels, during CO 2 PP [2,7,19]. One possible explanation is that the blood samples were not taken in chilled tubes.…”
Section: Discussionmentioning
confidence: 95%
“…The administration of 13-adrenergic drugs, such as dobutamine, induced a splanchnic blood flow redistribution, improving the intestinal mucosa microcirculation [1]. Renal effects secondary to increased intraabdominal pressure have been well analyzed [9,12,17]. It has been shown that impairment of renal function results from an ischemic effect caused by a sympathetically mediated intense renal vasoconstriction, with increases in both afferent and efferent arteriolar resistance [17].…”
mentioning
confidence: 99%
“…The use of carbon dioxide also results in its higher arterial and end-tidal levels [62]. The renal effects of pneumoperitoneum are similar to those reported in IAH [63,64,65,66,67,68,69]. The most frequently reported effect is oliguria [70].…”
Section: Special Situations With Laparoscopymentioning
confidence: 77%